Determination of Antioxidant and Antimicrobial Activity of Prickly lettuce (Lactuca serriola L.) Leaves Extract (Journal of the College of Basic Education, 2024)
The qualitative detection of active compounds in hot aqueous extract of Prickly lettuce (Lactuca serriola L.) leaves showed that it is rich with glycosides, alkaloids, terpenes, saponins, tannins, and flavonoids. The antioxidant activity (Inhibition %) was 9.35, 16.43, 29.17, 53.82, and 76.53% at 12.5, 25, 50, 100, and 200 mg/mL of extract, respectively; the LSD value was 7.053 that refer to found significant differences at (P≤0.05) in the concentrations used. The inhibition zones of Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Pseudomonas aeruginosa at (P≤0.05) were 12, 8, 9, and 6 mm, respectively, with average 8.75 mm and LSD value 2.703 at 12.5 mg/mL; 14, 10, 11 and 8 mm, respectively, with average 10.75 mm and LSD value 2.965 at 25 mg/mL; 18, 12, 15, and 11 mm, respectively, with average 14 mm and LSD value 3.071 at 50 mg/mL; 20, 13, 17, and 14 mm, respectively, with average 16 mm and LSD value 3.186 at 100 mg/mL, while, they were 22, 14, 19, and 16 mm, respectively, with average 17.75 mm and LSD value 3.622 at 200 mg/mL, the LSD values were 4.375, 3.502, 4.673, and 4.029 at (P≤0.05) for inhibition zone of S. aureus, B. cereus, E. coli, and P. aeruginosa, respectively, at 12.5, 25, 50, 100, and 200 mg of Prickly lettuce leaves extract.